PENGARUH KURS, EKSPOR, DAN IMPOR TERHADAP JUMLAH UANG BEREDAR DI INDONESIA DENGAN INFLASI SEBAGAI VARIABEL MODERATING 2011-2017 - Menhard Menhard (Institut Bisnis dan Teknologi Pelita Indonesia, 2018)
This research aims to determine and analyze the influence of currency on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of export on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of import on the money supply in Indonesia for the period of 2011-2017, to determine and analyze the influence of inflation on the money supply in Indonesia for the period of 2011-2017(moderating variable), to determine and analyze the influence of export and inflation on the money supply in Indonesia for the period of 2011-2017 (moderating variable), and to determine and analyze the influence of import and inflation on the money supply in Indonesia for the period of 2011-2017 (moderating variable). The research results stated that currency influences the money supply in Indonesia for the period of 2011-2017, export and import do not affect the money supply in Indonesia for the period of 2011-2017, currency and inflation not as moderating variable affect the money supply in Indonesia for the period of 2011-2017, export and inflation not as moderating variable affect the money supply in Indonesia for the period of 2011-2017, and import and inflation not as the moderating variable affect the money supply in Indonesia for the period of 2011-2017. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kurs terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh ekspor terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh impor terhadap jumlah uang beredar Indonesia tahun 2011 -2017, untuk mengetahui dan menganalisis pengaruh kurs dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating), untuk mengetahui dan menganalisis pengaruh ekspor dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating), dan untuk mengetahui dan menganalisis pengaruh impor dengan inflasi terhadap jumlah uang beredar Indonesia tahun 2011 -2017 (variabel moderating). Hasil penelitian ini menghasilkan penelitian diantaranya adalah kurs berpengaruh terhadap jumlah uang beredar Indonesia tahun 2011 -2017,ekspor dan impor tidak berpengaruh terhadap jumlah uang beredar Indonesia tahun 2011 -2017, kurs dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017,ekspor dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017, danImpor dengan inflasi tidak sebagai variabel moderating yang mempengaruhi terhadap jumlah uang beredar Indonesia tahun 2011 -2017.